BENEFITS DURING PREGNANCY HYDROGYMNASTICS WHO DEVELOPED LOW BACK PAIN (Fiep Bulletin - online, 2011)
This work is an objective study on the benefits of water exercise during pregnancy. Talks about gymnastics and its techniques. Explains the concept of exercises done in water, which is formed from man's need to create a low-impact time to exercise. Focuses a little history of gymnastics. Demonstrates how these exercises done in water are capable of doing in pregnant women, facilitating the practice of movements out of the water are difficult for them. Brings a discussion regarding the care for pregnant women - this involves special care - in the exercise prescription. The object of the research is to highlight the aspect of the pregnant women need the application of physical exercise - water aerobics. The paper discusses the concepts on the gestational period studied within their needs, from their first symptoms until the stage that features the first pain - specifically the lumbar. What is an aquatic exercise for a pregnant woman with back pain was the starting point the idea of research. A whole sequence was developed through a literature review to substantiate the arguments and facts on the basis of the study. An analysis was made in respect of pregnant and gymnastics. Reflecting on results, the benefits of gymnastics in pregnant women were shown in the shot of the research forming the top job. Pregnancy is not a disease, if everything is normal, the exercise will help, and water is the ideal medium for this. Therefore, for water is perfectly adequate for the gestational period.
Keywords: Aquatic; pregnancy; low back pain